The Influence of Digital Financial Literacy and Security on Customer Decisions in Using the Livin by Mandiri Application (A Study at Bank Mandiri KCP Donggala) - Ammar; Irham Pakkawaru; Asriyana; Ikmar Masykur; nizmayavira (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2025)
The development of digital technology has changed the pattern of banking services, including the use of mobile banking applications such as Livin' by Mandiri. This application offers convenience in transactions, but customer trust in using it is inseparable from the digital financial literacy and security factors of the system offered. Digital financial literacy plays a role in helping customers understand the features, risks, and benefits of the application, while the security aspect determines the customer's sense of security in transactions. This study aims to analyze the influence of digital financial literacy and security on customer decisions in using the Livin' by Mandiri application at Bank Mandiri KCP Donggala. This study uses a quantitative approach with a survey method by distributing questionnaires to Bank Mandiri KCP Donggala customers. The study population is all customers who use the Livin' by Mandiri application, with probability sampling techniques and simple random sampling types. The data obtained were analyzed using multiple linear regression tests, T tests for partial effect testing, and F tests (ANOVA) for simultaneous effect testing with the help of SPSS software. Based on the test results, the digital financial literacy variable (X1) has a positive and significant partial effect on customer decisions with a Tcount value of 2.416 > Ttable 1.985 and a significance of 0.018 < 0.05. The security variable (X2) also has a positive and significant partial effect with a Tcount value of 3.683 > Ttable 1.985 and a significance of 0.000 < 0.05. Simultaneously, digital financial literacy and security have a significant effect on customer decisions with a significance value of 0.000 < 0.05 and Fcount 29.334 > Ftable 3.09. This proves that digital financial literacy and security are important factors in customer decision making to use Livin by Mandiri